Polymer films and laminates
The polymer film with expandable layers and controlled thermal expansion addresses adhesion issues in conventional films, enhancing bonding and reducing transmission loss for high-frequency applications.
Patent Information
- Application Number
- JP2020194653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-24
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-11-24
AI Technical Summary
Conventional polymer films and laminates exhibit poor adhesion to other polymer films and metal foils, leading to issues with interlayer adhesion and transmission loss in high-frequency applications.
A polymer film with layers that can expand in volume by external stimulation, featuring a dielectric loss tangent of 0.005 or less, and a thermal expansion coefficient difference between layers to enhance adhesion, incorporating a blowing agent and fillers to achieve better bonding.
The polymer film demonstrates excellent adhesion to other polymer films and metal foils, reducing transmission loss and improving interlayer adhesion, suitable for high-frequency applications.
Smart Images

Figure 0007617729000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to polymer films and laminates. [Background technology]
[0002] In recent years, the frequencies used in communication devices have tended to become very high. In order to suppress transmission loss in the high frequency band, there is a demand for insulating materials used in circuit boards to have low relative dielectric constants and dielectric loss tangents. Conventionally, polyimide has been widely used as an insulating material for circuit boards, but liquid crystal polymers, which have high heat resistance, low water absorption, and small loss in high frequency bands, have been attracting attention.
[0003] As an example of a conventional polymer film, Patent Document 1 describes a liquid crystal polyester film containing at least a liquid crystal polyester, in which when a first orientation degree is an orientation degree in a first direction parallel to a main surface of the liquid crystal polyester film and a second orientation degree is an orientation degree in a second direction parallel to the main surface and perpendicular to the first direction, the ratio of the first orientation degree to the second orientation degree, that is, first orientation degree / second orientation degree, is 0.95 or more and 1.04 or less, and the third orientation degree of the liquid crystal polyester measured by wide-angle X-ray scattering in a direction parallel to the main surface is 60.0% or more.
[0004] Furthermore, as a conventional peelable laminate film, the one described in Patent Document 2 is known. Patent Document 2 describes a peelable laminate film having a laminate including a layer A containing a cellulose ester and a layer B containing a solution-formable resin different from the cellulose ester, and characterized in that the adhesion between layer A and layer B is 5 N / cm or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-26474 A [Patent Document 2] JP 2013-46992 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of one embodiment of the present invention is to provide a polymer film that has excellent adhesion to other polymer films and metal foils. Another problem to be solved by the present invention is to provide a laminate using the above polymer film, which has excellent interlayer adhesion. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> A polymer film having a layer A and a layer B on at least one surface of the layer A, wherein at least one of the layer A and the layer B is a layer capable of volumetric expansion in response to an external stimulus, and has a dielectric loss tangent of 0.005 or less. <2> The layer B is a layer capable of expanding in volume by the external stimulus. <1> The polymer film according to claim 1. <3> The expansion coefficient of the layer B at 160°C is 0.1% or more. <2> The polymer film according to claim 1. <4> The expansion coefficient of the layer B at 300°C is 0.1% or more. <2> or <3> The polymer film according to claim 1. <5> The expansion coefficient of the layer B at 300°C is greater than the expansion coefficient of the layer A at 300°C. <2> ~ <4> 13. The polymer film according to claim 12, <6> The thermal expansion coefficient αs of the layer B is greater than the thermal expansion coefficient αc of the layer A. <1> ~ <5> 13. The polymer film according to claim 12, <7> The layer B contains a foaming agent. <1> ~ <6> 13. The polymer film according to claim 12, <8> The polymer film contains a filler in any layer. <1> ~ <7> 13. The polymer film according to claim 12, <9> The number density of the filler is greater inside the polymer film than on the surface. <8> The polymer film according to claim 1. <10> The layer B contains a filler. <8> or <9> The polymer film according to claim 1. <11> The layer B contains needle-like fillers or fillers having protrusions. <10> The polymer film according to claim 1. <12> The linear expansion coefficient of the polymer film is -20 ppm / K to 50 ppm / K. <1> ~ <11> 13. The polymer film according to claim 12, <13> The dielectric loss tangent of the polymer film is 0.004 or less. <1> ~ <12> 13. The polymer film according to claim 12, <14> The polymer film contains a liquid crystal polymer in any of its layers. <1> ~ <13> 13. The polymer film according to claim 12, <15> The liquid crystal polymer has a repeating unit represented by any one of formulas (1) to (3). <14> The polymer film according to claim 1. Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), X and Y each independently represent an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the above group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 - In formula (4), Ar 4 and Ar 5each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group. <16> Further comprising a layer C, and comprising the layer B, the layer A, and the layer C in this order. <1> ~ <15> 13. The polymer film according to claim 12, <17> <1> ~ <16> and a copper layer disposed on the surface of the polymer film on the Layer B side. <18> The average thickness of the layer B is greater than the average thickness of the copper layer. <17> The laminate according to claim 1. <19> The peel strength between the layer B and the copper layer is 0.5 kN / m or more. <17> or <18> The laminate according to claim 1. <20> <16> a copper layer disposed on a surface of the polymer film facing the layer B; and a copper layer disposed on a surface of the polymer film facing the layer C. <21> The peel strength between the layer C and the copper layer disposed on the surface of the layer C is 0.5 kN / m or more. <20> The laminate according to claim 1. Effect of the Invention
[0008] According to one embodiment of the present invention, it is possible to provide a polymer film that has excellent adhesion to other polymer films and metal foils. According to another embodiment of the present invention, a laminate having excellent interlayer adhesion and using the above polymer film can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The contents of the present disclosure will be described in detail below. The following description of the components may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In addition, in the description of groups (atomic groups) in this specification, descriptions that do not indicate whether they are substituted or unsubstituted include those that have no substituents as well as those that have a substituent. For example, an "alkyl group" includes not only an alkyl group that has no substituents (unsubstituted alkyl groups) but also an alkyl group that has a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used as a concept including both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl. In addition, the term "step" in this specification includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In addition, in this disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Furthermore, in the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are molecular weights detected by a gel permeation chromatography (GPC) analyzer using a column of TSKgel SuperHM-H (product name of Tosoh Corporation) in a solvent of PFP (pentafluorophenol) / chloroform = 1 / 2 (mass ratio) and a differential refractometer, and converted using polystyrene as a standard substance.
[0010] (Polymer film) The polymer film according to the present disclosure has a layer A and a layer B on at least one surface of the layer A, wherein at least one of the layer A and the layer B is a layer that is volumetrically expandable in response to an external stimulus and has a dielectric loss tangent of 0.005 or less.
[0011] The inventors have found that conventional polymer films have a low content of polar groups, and therefore do not have sufficient adhesion to other polymer films and metal foils, and that in flexible wiring boards produced by laminating and patterning a polymer film and a metal foil and further laminating them, there are areas with poor interlayer adhesion. As a result of extensive investigations, the present inventors have found that the above-mentioned structure makes it possible to provide a polymer film having excellent adhesion to metal foil. Although the detailed mechanism by which the above effects are obtained is unclear, it is speculated as follows. The film has a layer A and a layer B on at least one side of the layer A, and at least one of the layers A and B is a layer that can expand in volume in response to an external stimulus. This is believed to enable the volume of the volume-expandable layer to expand in volume in response to the external stimulus in areas of localized pressure drop (poor adhesion) that occurs when the film is laminated to a patterned metal foil laminate (in which a metal foil portion and another polymer film portion are present on the surface), and to further increase the pressure for adhesion, resulting in excellent adhesion to other polymer films and metal foils.
[0012] <<Dielectric tangent>> The polymer film according to the present disclosure has a dielectric tangent of 0.005 or less, and from the viewpoint of reducing the transmission loss of the produced substrate, it is preferably 0.004 or less, more preferably 0.0035 or less, and particularly preferably greater than 0 and 0.003 or less.
[0013] From the viewpoint of reducing the transmission loss of the produced substrate, the dielectric tangent of Layer A in the polymer film according to the present disclosure is preferably 0.005 or less, more preferably 0.004 or less, even more preferably 0.0035 or less, and particularly preferably greater than 0 and 0.003 or less.
[0014] The dielectric loss tangent of Layer B in the polymer film according to the present disclosure is preferably 0.01 or less, more preferably 0.005 or less, even more preferably 0.004 or less, and particularly preferably greater than 0 and 0.003 or less, from the viewpoints of reducing the transmission loss of the produced substrate and of adhesion to other polymer films and metal foils.
[0015] The dielectric tangent in this disclosure is measured by the following method. The dielectric constant is measured by the resonance perturbation method at a frequency of 10 GHz. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd. CP531) is connected to a network analyzer (Agilent Technology Co., Ltd. "E8363B"), and a polymer film or each layer sample (width: 2.0 mm x length: 80 mm) is inserted into the cavity resonator. The dielectric constant and dielectric loss tangent of the polymer film or each layer are measured from the change in resonance frequency before and after insertion for 96 hours in an environment of 25°C temperature and 60% RH.
[0016] <<Expansion rate>> In the polymer film according to the present disclosure, at least one of the layer A and the layer B may be a layer capable of volume expansion in response to an external stimulus. From the viewpoint of adhesion to other polymer films and metal foils, however, it is preferable that the layer B be a layer capable of volume expansion in response to an external stimulus.
[0017] From the viewpoints of adhesion to other polymer films and metal foils and low-temperature application, the expansion coefficient of Layer B at 160°C is preferably 0.1% or more, more preferably 1% or more, even more preferably 3% or more and 100% or less, and particularly preferably 5% or more and 70% or less. From the viewpoint of adhesion to other polymer films and metal foils, the expansion coefficient of Layer B at 300°C is preferably 0.1% or more, more preferably 3% or more, even more preferably 5% or more and 100% or less, and particularly preferably 10% or more and 70% or less. From the viewpoint of adhesion to other polymer films and metal foils, the expansion coefficient of Layer B at 160°C is preferably larger than the expansion coefficient of Layer A at 160°C, and the difference in the expansion coefficient between Layer A and Layer B is preferably 0.1% or more, more preferably 1% or more, even more preferably 3% or more and 100% or less, and particularly preferably 5% or more and 70% or less. Furthermore, from the viewpoint of adhesion to other polymer films and metal foils, the expansion coefficient of Layer B at 300°C is preferably larger than the expansion coefficient of Layer A at 300°C, and the difference in the expansion coefficient between Layer A and Layer B is preferably 0.1% or more, more preferably 3% or more, even more preferably 5% or more and 100% or less, and particularly preferably 10% or more and 70% or less.
[0018] The expansion rate in this disclosure is measured by the following method. The polymer film is cut with a microtome to prepare slice samples, and the thickness changes of layers A and B are measured using an optical microscope equipped with a heating stage system (HS82, Mettler Toledo). The initial thickness (t25) at 25°C and the thickness (t160) when heated to 160°C at a rate of 10°C / min are evaluated, and the value divided by the initial thickness (t160 / t25) is calculated as the expansion coefficient at 160°C (unit: %). The same calculation is performed for 300°C.
[0019] <<Thermal expansion coefficient>> In the polymer film according to the present disclosure, the thermal expansion coefficient of the layer capable of volumetric expansion in response to an external stimulus is preferably greater than the thermal expansion coefficient of the layer that is not capable of volumetric expansion in response to an external stimulus. When Layer B is a layer capable of volume expansion by an external stimulus, it is preferable that Layer B has a thermal expansion coefficient αs larger than Layer A's thermal expansion coefficient αc from the viewpoint of adhesion to other polymer films and metal foils.
[0020] The thermal expansion coefficient of the layer that can expand in volume in response to an external stimulus is preferably 50 ppm / K or more, more preferably 60 ppm / K to 300 ppm / K, and particularly preferably 70 ppm / K to 250 ppm / K, from the viewpoint of adhesion to other polymer films and metal foils. Furthermore, when Layer B is a layer capable of volume expansion in response to an external stimulus, the thermal expansion coefficient αs of Layer B is preferably 50 ppm / K or more, more preferably 60 ppm / K to 300 ppm / K, and particularly preferably 70 ppm / K to 250 ppm / K, from the viewpoint of adhesion to other polymer films and metal foils. When Layer A is not a layer that can expand in volume due to an external stimulus, the thermal expansion coefficient αc of Layer A is not particularly limited, but from the viewpoint of adhesion to other polymer films and metal foils, it is preferably -20 ppm / K or more, more preferably 0 ppm / K or more, even more preferably 30 ppm / K or more, and particularly preferably 50 ppm / K to 100 ppm / K.
[0021] The thermal expansion coefficient of each layer in the present disclosure is measured by the following method. The polymer film is cut with a microtome to prepare a section sample, and is set in an optical microscope equipped with a heating stage system (HS82, Mettler Toledo). Next, the temperature is raised from 25 to 200°C at a rate of 5°C / min, then cooled to 30°C at a rate of 20°C / min, and then heated again at a rate of 5°C / min. The thickness of layer B at 30°C (ts30) and the thickness of layer B at 150°C (ts150) are evaluated, and the value obtained by dividing the dimensional change by the temperature change ((ts150-ts30) / (150-30)) is calculated as the thermal expansion coefficient (αs) of layer B. The thermal expansion coefficient (αc) of layer A is also calculated in the same manner.
[0022] <<Layer that can expand in volume in response to external stimuli>> In the polymer film according to the present disclosure, at least one of Layer A and Layer B is a layer capable of volumetric expansion in response to an external stimulus. The external stimulus is not particularly limited, and can be appropriately selected depending on a known volume expansion method. Specific examples of the external stimulus include heat, pressure, an electric field, sound waves, electromagnetic waves (including light), and a magnetic field. Among these, from the viewpoints of ease of laminate preparation, low dielectric tangent, and adhesion to other polymer films and metal foils, at least one external stimulus selected from the group consisting of heat, pressure, and electromagnetic waves is more preferable, at least one external stimulus selected from the group consisting of heat and pressure is more preferable, and heat is particularly preferable.
[0023] The layer capable of expanding in volume in response to an external stimulus preferably contains a foaming agent, from the viewpoints of ease of handling and storage of the polymer film. For example, when Layer B is a layer capable of volume expansion in response to an external stimulus, Layer B preferably contains a foaming agent. The foaming agent is not particularly limited, and any known foaming agent can be used. Either a physical foaming agent or a chemical foaming agent can be used. From the viewpoint of the handling and storage properties of the polymer film, however, a chemical foaming agent is preferable. From the viewpoints of low dielectric tangent and adhesion to the metal foil, the foaming agent is preferably a foaming agent that decomposes when heated, and the decomposition temperature can be appropriately selected depending on the lamination temperature at the time of attachment, etc., but is preferably 100° C. to 300° C., and more preferably 100° C. to 160° C. From the viewpoint of storage stability, the decomposition temperature is preferably 200° C. to 300° C. The chemical foaming agent may be an inorganic compound or an organic compound, and two or more kinds may be used in combination. Examples of organic chemical foaming agents include nitrosamine compounds such as dinitrosopentamethylenetetramine (DPT), azo compounds such as azodicarbonamide (ADCA), and hydrazine compounds such as 4,4'-oxybisbenzenesulfonylhydrazide (OBSH) and hydrazodicarbonamide (HDCA). Examples of inorganic chemical foaming agents include hydrogen carbonates such as sodium hydrogen carbonate, carbonates, and combinations of hydrogen carbonates and organic acid salts such as sodium citrate. Among these, from the viewpoints of low dielectric tangent, adhesion to metal foil, and ease of handling and storage of the polymer film, inorganic chemical foaming agents are preferred, a combination of a hydrogen carbonate and an organic acid salt is more preferred, and a combination of sodium hydrogen carbonate and sodium citrate is particularly preferred.
[0024] The foaming agent may be used alone or in combination of two or more kinds. The content of the foaming agent in the layer capable of volumetric expansion in response to an external stimulus is preferably 0.01% by mass to 30% by mass, more preferably 0.05% by mass to 20% by mass, and particularly preferably 0.5% by mass to 15% by mass, relative to the total mass of the layer capable of volumetric expansion in response to an external stimulus, from the viewpoints of low dielectric tangent, adhesion to the metal foil, and ease of handling and storage of the polymer film.
[0025] The layer capable of volumetric expansion in response to an external stimulus preferably contains a liquid crystal polymer. The layer capable of expanding in volume in response to an external stimulus may contain other components. As the liquid crystal polymer and other components in the layer capable of expanding in volume in response to an external stimulus, the liquid crystal polymer and other components described in Layer A and Layer B described below can be suitably used. The preferred embodiment of the average thickness of the layer capable of volumetrically expanding in response to an external stimulus is the same as that of Layer A or Layer B described below.
[0026] From the viewpoint of handling and storage stability of the polymer film, the layer capable of volume expansion by an external stimulus also preferably contains a polymer having a linear expansion coefficient larger than that of the liquid crystal polymer contained in Layer A. By containing the polymer having a large linear expansion coefficient, the layer can be made to be capable of volume expansion by heat. Preferred examples of the polymer having a large linear expansion coefficient include silicone rubber, silicone resin, polyethylene, cycloolefin polymers, and amorphous polyester.
[0027] The polymers having a large linear expansion coefficient may be used alone or in combination of two or more kinds. The content of the polymer having a large linear expansion coefficient in the layer capable of expanding in volume in response to an external stimulus is preferably 1% by mass to 90% by mass, more preferably 5% by mass to 80% by mass, even more preferably 10% by mass to 70% by mass, and particularly preferably 20% by mass to 60% by mass, based on the total mass of the layer capable of expanding in volume in response to an external stimulus, from the viewpoints of low dielectric tangent, adhesion to the metal foil, and ease of handling and storage of the polymer film.
[0028] <Layer A> The polymer film according to the present disclosure has a layer A and a layer B on at least one side of the layer A. From the viewpoint of a low dielectric tangent, it is preferable that either layer contains a liquid crystal polymer, it is more preferable that the layer A contains a liquid crystal polymer, it is particularly preferable that the layer A and the layer B each contain a liquid crystal polymer, and it is most preferable that the layer A and the layer B contain the same type of liquid crystal polymer. Layer A may be a layer whose volume is expandable by an external stimulus, but from the viewpoints of the thermal expansion coefficient and low dielectric tangent, it is preferable that layer A is not a layer whose volume is expandable by an external stimulus.
[0029] -Liquid crystal polymer- In the present disclosure, the type of liquid crystal polymer is not particularly limited, and any known liquid crystal polymer can be used. The liquid crystal polymer may be a thermotropic liquid crystal polymer that exhibits liquid crystallinity in a molten state, or a lyotropic liquid crystal polymer that exhibits liquid crystallinity in a solution state. In the case of a thermotropic liquid crystal, it is preferable that the liquid crystal polymer melts at a temperature of 450° C. or less. Examples of the liquid crystal polymer include liquid crystal polyester, liquid crystal polyester amide in which an amide bond is introduced into a liquid crystal polyester, liquid crystal polyester ether in which an ether bond is introduced into a liquid crystal polyester, and liquid crystal polyester in which a carbonate bond is introduced into a liquid crystal polyester. Examples include styrene carbonate. From the viewpoints of liquid crystallinity and thermal expansion coefficient, the liquid crystal polymer is preferably a polymer having an aromatic ring, and more preferably an aromatic polyester or an aromatic polyester amide. Furthermore, the liquid crystal polymer may be a polymer in which an imide bond, a carbodiimide bond, or a bond derived from an isocyanate such as an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide. The liquid crystal polymer is preferably a wholly aromatic liquid crystal polymer made using only aromatic compounds as raw material monomers.
[0030] Examples of liquid crystal polymers include, for example: 1) (i) A compound obtained by polycondensation of an aromatic hydroxycarboxylic acid, (ii) an aromatic dicarboxylic acid, and (iii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 2) Those obtained by polycondensation of multiple types of aromatic hydroxycarboxylic acids. 3) (i) a polycondensation product of an aromatic dicarboxylic acid and (ii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 4) (i) Polyester such as polyethylene terephthalate and (ii) aromatic hydroxycarboxylic acid are polycondensed. Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may each independently be replaced in whole or in part by a polycondensable derivative thereof.
[0031] Examples of polymerizable derivatives of compounds having a carboxy group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include those in which the carboxy group has been converted to an alkoxycarbonyl group or an aryloxycarbonyl group (esters), those in which the carboxy group has been converted to a haloformyl group (acid halides), and those in which the carboxy group has been converted to an acyloxycarbonyl group (acid anhydrides). Examples of polymerizable derivatives of compounds having a hydroxy group, such as aromatic hydroxycarboxylic acids, aromatic diols and aromatic hydroxyamines, include those obtained by acylation of a hydroxy group into an acyloxy group (acylated products). Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxyamines and aromatic diamines, include those obtained by acylation of the amino group to an acylamino group (acylated product).
[0032] From the viewpoints of liquid crystallinity, thermal expansion coefficient, and adhesion to metal foil, the liquid crystal polymer preferably has a constituent repeating unit represented by any one of the following formulas (1) to (3) (hereinafter, the constituent repeating unit represented by formula (1) etc. may be referred to as repeating unit (1) etc.), more preferably has a constituent repeating unit represented by the following formula (1), and particularly preferably has a constituent repeating unit represented by the following formula (1), a constituent repeating unit represented by the following formula (2), and a constituent repeating unit represented by the following formula (2). Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), X and Y each independently represent an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the above group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 - In formula (4), Ar 4 and Ar 5each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
[0033] The halogen atom includes a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group, and the number of carbon atoms is preferably 1 to 10. Examples of the aryl group include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group, and the number of carbon atoms is preferably 6 to 20. When the hydrogen atoms are replaced with these groups, the number of them is Ar 1 , Ar 2 Or Ar 3 The number of each of the above groups represented by the following formula (I) is preferably 2 or less, and more preferably 1.
[0034] Examples of the alkylene group include a methylene group, a 1,1-ethanediyl group, a 1-methyl-1,1-ethanediyl group, a 1,1-butanediyl group, and a 2-ethyl-1,1-hexanediyl group, and the number of carbon atoms is preferably 1 to 10.
[0035] The repeating unit (1) is a constituent repeating unit derived from a specific aromatic hydroxycarboxylic acid. The repeating unit (1) is Ar 1 is a p-phenylene group (constituent repeating unit derived from p-hydroxybenzoic acid), and Ar 1 is preferably a 2,6-naphthylene group (a repeating unit derived from 6-hydroxy-2-naphthoic acid) or a 4,4'-biphenylylene group (a repeating unit derived from 4'-hydroxy-4-biphenylcarboxylic acid).
[0036] The repeating unit (2) is a constituent repeating unit derived from a specific aromatic dicarboxylic acid. Repeating unit (2) is Ar 2 is a p-phenylene group (constituent repeating unit derived from terephthalic acid), Ar 2 is an m-phenylene group (a repeating unit derived from isophthalic acid), Ar 2 is a 2,6-naphthylene group (a repeating unit derived from 2,6-naphthalenedicarboxylic acid), or Ar 2 is a diphenylether-4,4'-diyl group (constituent repeating unit derived from diphenylether-4,4'-dicarboxylic acid).
[0037] The repeating unit (3) is a constituent repeating unit derived from a specific aromatic diol, aromatic hydroxylamine or aromatic diamine. Repeating unit (3) is Ar 3 is a p-phenylene group (constituent repeating units derived from hydroquinone, p-aminophenol or p-phenylenediamine), Ar 3 is an m-phenylene group (a repeating unit derived from isophthalic acid), or Ar 3 is a 4,4'-biphenylylene group (a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0038] The content of the repeating unit (1) is preferably 30 mol % or more, more preferably 30 mol % to 80 mol %, even more preferably 30 mol % to 60 mol %, and particularly preferably 30 mol % to 40 mol %, based on the total amount of all constituent repeating units (the mass of each constituent repeating unit constituting the liquid crystal polymer is divided by the formula weight of that repeating unit to determine the substance amount equivalent (mol) of each repeating unit, and the total value). The content of the repeating unit (2) is preferably 35 mol % or less, more preferably 10 mol % to 35 mol %, even more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total amount of all constituent repeating units. The content of the repeating unit (3) is preferably 35 mol % or less, more preferably 10 mol % to 35 mol %, still more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total amount of all constituent repeating units. The greater the content of the repeating unit (1), the more likely it is that the heat resistance, strength and rigidity will improve. However, if the content is too high, the solubility in solvents will tend to decrease.
[0039] The ratio of the content of the repeating unit (2) to the content of the repeating unit (3), expressed as [content of the repeating unit (2)] / [content of the repeating unit (3)] (mol / mol), is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.
[0040] The liquid crystal polymer may have two or more kinds of repeating units (1) to (3) independently. The liquid crystal polymer may have a constituent repeating unit other than the repeating units (1) to (3), but the content of such a repeating unit is preferably 10 mol % or less, more preferably 5 mol % or less, based on the total amount of all repeating units.
[0041] The liquid crystal polymer preferably has, as the repeating unit (3), at least one of X and Y being an imino group, i.e., at least one of a constituent repeating unit derived from a specific aromatic hydroxylamine and a constituent repeating unit derived from an aromatic diamine, since this has excellent solubility in a solvent, and more preferably has, as the repeating unit (3), only those in which at least one of X and Y is an imino group.
[0042] The liquid crystal polymer is preferably produced by melt-polymerizing the raw material monomers corresponding to the repeating units constituting the polymer. The melt-polymerization may be carried out in the presence of a catalyst, and examples of the catalyst include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole, and nitrogen-containing heterocyclic compounds are preferably used. The melt-polymerization may be further carried out as necessary by solid-phase polymerization.
[0043] The liquid crystal polymer has a flow initiation temperature of preferably 250° C. or higher, more preferably 250° C. or higher and 350° C. or lower, and further preferably 260° C. or higher and 330° C. or lower. When the flow initiation temperature of the liquid crystal polymer is within the above range, the liquid crystal polymer has excellent solubility, heat resistance, strength and rigidity, and the viscosity of the solution is appropriate.
[0044] The flow initiation temperature is also called the flow temperature or flow temperature, and is measured using a capillary rheometer at 9.8 MPa (100 kg / cm 2 When a liquid crystal polymer is melted and extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm while heating at a rate of 4°C / min under a load of 100 g / mol / L, the temperature at which the polymer shows a viscosity of 4,800 Pa s (48,000 poise) is reached, and this temperature is an indication of the molecular weight of the liquid crystal polymer (see "Liquid Crystal Polymer - Synthesis, Molding, Applications" edited by Koide Naoyuki, CMC Corporation, June 5, 1987, p. 95).
[0045] The liquid crystal polymer preferably has a weight average molecular weight of 1,000,000 or less, more preferably 3,000 to 300,000, even more preferably 5,000 to 100,000, and particularly preferably 5,000 to 30,000. When the weight average molecular weight of the liquid crystal polymer is within the above range, the film after heat treatment has excellent thermal conductivity in the thickness direction, heat resistance, strength, and rigidity.
[0046] The liquid crystal polymer is preferably a liquid crystal polymer that is soluble in a specific organic solvent (hereinafter, also referred to as a "soluble liquid crystal polymer"). Specifically, the soluble liquid crystal polymer in the present disclosure is a liquid crystal polymer that dissolves at 25°C in an amount of 0.1 g or more in 100 g of at least one solvent selected from the group consisting of N-methylpyrrolidone, N-ethylpyrrolidone, dichloromethane, dichloroethane, chloroform, N,N-dimethylacetamide, γ-butyrolactone, dimethylformamide, ethylene glycol monobutyl ether, and ethylene glycol monoethyl ether.
[0047] The layer A may contain only one type of liquid crystal polymer, or may contain two or more types of liquid crystal polymers. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the content of the liquid crystal polymer in Layer A is preferably 20 volume % to 100 volume %, more preferably 20 volume % to 100 volume %, even more preferably 30 volume % to 100 volume %, and particularly preferably 40 volume % to 100 volume %, relative to the total volume of Layer A.
[0048] -Filler- From the viewpoints of the thermal expansion coefficient and adhesion to other polymer films and metal foils, the polymer film preferably contains a filler in at least one layer, and more preferably layer A contains a filler. The filler may be particulate or fibrous, and may be an inorganic filler or an organic filler. In the polymer film according to the present disclosure, the number density of the filler is preferably greater inside than on the surface, from the viewpoint of suppressing distortion of the metal wiring when adhered to the metal wiring.
[0049] As the inorganic filler, a known inorganic filler can be used. Examples of the inorganic filler material include BN, Al2O3, AlN, TiO2, SiO2, barium titanate, strontium titanate, aluminum hydroxide, calcium carbonate, and materials containing two or more of these. Among these, as the inorganic filler, from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, metal oxide particles or fibers are preferred, silica particles, titania particles, or glass fibers are more preferred, and silica particles or glass fibers are particularly preferred. From the viewpoints of thermal expansion coefficient and adhesion to the metal foil, the average particle size of the inorganic filler is preferably 5 nm to 20 μm, more preferably 10 nm to 10 μm, further preferably 20 nm to 1 μm, and particularly preferably 25 nm to 500 nm. In the case where the particles or fibers are flat, the average particle size indicates the length in the short side direction.
[0050] As the organic filler, a known organic filler can be used. Examples of the organic filler material include polyethylene, polystyrene, urea-formalin filler, polyester, cellulose, acrylic resin, fluororesin, hardened epoxy resin, crosslinked benzoguanamine resin, crosslinked acrylic resin, and materials containing two or more of these. The organic filler may be in the form of fibers such as nanofibers, or may be in the form of hollow resin particles. Among these, from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the organic filler is preferably fluororesin particles, polyester-based resin particles, or nanofibers of cellulose-based resin, and more preferably polytetrafluoroethylene particles. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the average particle size of the organic filler is preferably 5 nm to 20 μm, more preferably 10 nm to 1 μm, further preferably 20 nm to 500 nm, and particularly preferably 25 nm to 90 nm.
[0051] Layer A may contain only one type of filler, or may contain two or more types of fillers. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the content of the filler in Layer A is preferably 5 volume % to 80 volume %, more preferably 10 volume % to 70 volume %, even more preferably 20 volume % to 70 volume %, and particularly preferably 30 volume % to 60 volume %, relative to the total volume of Layer A.
[0052] -Other additives- The layer A may contain additives other than the liquid crystal polymer and the filler. As the other additives, known additives can be used, specifically, for example, a leveling agent, a defoaming agent, an antioxidant, an ultraviolet absorbing agent, a flame retardant, a colorant, etc.
[0053] Furthermore, the layer A may contain, as other additives, resins other than the above-mentioned components. Examples of resins other than liquid crystal polymers include thermoplastic resins such as polyolefins, cycloolefin polymers, polyamides, polyesters, polyphenylene sulfide, polyether ketones, polycarbonates, polyether sulfones, polyphenylene ethers and modified products thereof, polyether imides, silicone resins, and fluorine-based resins; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, and cyanate resins.
[0054] The total content of other additives in Layer A is preferably 25 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the liquid crystal polymer.
[0055] The average thickness of Layer A is not particularly limited, but from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, it is preferably 5 μm to 90 μm, more preferably 10 μm to 70 μm, and particularly preferably 15 μm to 50 μm.
[0056] The method for measuring the average thickness of each layer in the polymer film according to the present disclosure is as follows. The polymer film is cut with a microtome, and the cross section is observed under an optical microscope to evaluate the thickness of each layer. Cross-sectional samples are cut out in three or more places, and the thickness is measured at three or more points on each cross section, and the average of these measurements is taken as the average thickness. The polymer film is cut in a plane perpendicular to the plane direction of the polymer film, the thickness is measured at five or more points on the cross section, and the average value of the measurements is regarded as the average thickness.
[0057] <Layer B> The polymer film according to the present disclosure has a layer A and a layer B on at least one side of the layer A. Moreover, Layer B is preferably a surface layer (outermost layer). Furthermore, from the viewpoint of adhesion to the metal foil, Layer B is preferably a layer capable of expanding in volume in response to an external stimulus.
[0058] From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, it is preferable that Layer B contains a liquid crystal polymer. A preferred embodiment of the liquid crystal polymer used in Layer B is the same as that used in Layer A, except as described below. The liquid crystal polymer contained in Layer B may be the same as or different from the liquid crystal polymer contained in Layer A, but is preferably the same as the liquid crystal polymer contained in Layer A.
[0059] The content of the liquid crystal polymer in Layer B is preferably smaller than the content of the liquid crystal polymer in Layer A from the viewpoints of the thermal expansion coefficient and the adhesion to the metal foil. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the content of the liquid crystal polymer in Layer B is preferably 10% by mass to 99.99% by mass, more preferably 20% by mass to 99.9% by mass, even more preferably 30% by mass to 95% by mass, and particularly preferably 30% by mass to 90% by mass, relative to the total mass of Layer B.
[0060] From the viewpoint of adhesion to the metal foil, Layer B preferably contains a filler, and more preferably contains a needle-like filler or a filler having protrusions. Preferred embodiments of the filler used in Layer B are the same as those of the filler used in Layer A, except as described below. The needle-like filler is preferably an inorganic needle-like filler, and more preferably an inorganic oxide needle-like filler. The aspect ratio of the needle filler is preferably 3 or more, more preferably 5 or more, and particularly preferably 5 or more and 100 or less. As the filler having protrusions, an inorganic filler having protrusions is preferable, and an inorganic oxide filler having protrusions is more preferable. As a filler having protrusions, a confetti-shaped filler (star-shaped rock candy, Japanese confection having horned protrusions on the surface of a spherical shape) is more preferable. A suitable example of the confetti-shaped filler is the confetti-shaped silica sol described in JP-A-2008-169102. From the viewpoint of adhesion to the metal foil, the average particle size of the needle-like filler and the filler having protrusions is preferably 5 nm to 20 μm, more preferably 10 nm to 1 μm, even more preferably 20 nm to 500 nm, and particularly preferably 25 nm to 90 nm.
[0061] When Layer A contains a filler, the content of the filler in Layer B is preferably lower than the content of the filler in Layer A from the viewpoints of the thermal expansion coefficient and the adhesion to the metal foil. When Layer B contains a filler, the content of the filler in Layer B is preferably 1 mass % to 70 mass %, more preferably 5 mass % to 60 mass %, and particularly preferably 10 mass % to 55 mass %, relative to the total mass of Layer B, from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil.
[0062] Layer B may contain other additives in addition to the liquid crystal polymer, the foaming agent and the filler. Preferred embodiments of the other additives used in Layer B are the same as those of the other additives used in Layer A, except as described below.
[0063] The average thickness of Layer B is preferably smaller than the average thickness of Layer A from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil. Average thickness T of layer A A and the average thickness T of layer B B T A / T B From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the value of is preferably greater than 1, more preferably 1.5 to 100, further preferably 2 to 10, and particularly preferably 2 to 5. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the average thickness of Layer B is preferably 3 μm to 40 μm, more preferably 5 μm to 30 μm, even more preferably 8 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Furthermore, when Layer B is a layer capable of volume expansion in response to an external stimulus, the average thickness of Layer B is preferably greater than the average thickness of a copper layer (copper wiring) in the laminate described below.
[0064] <Layer C> The polymer film according to the present disclosure preferably further has a Layer C, and more preferably has the Layer B, the Layer A, and the Layer C in this order. Moreover, the layer C is preferably a surface layer (outermost layer). Furthermore, layer C may be a layer that is volume-expandable in response to an external stimulus. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the layer C preferably contains a liquid crystal polymer. A preferred embodiment of the liquid crystal polymer used in the layer C is the same as that of the liquid crystal polymer used in the layer A, except as described below. The liquid crystal polymer contained in layer C may be the same as or different from the liquid crystal polymer contained in layer A or layer B, but is preferably the same as the liquid crystal polymer contained in layers A and B.
[0065] The content of the liquid crystal polymer in Layer C is preferably smaller than the content of the liquid crystal polymer in Layer A from the viewpoints of the thermal expansion coefficient and the adhesion to the metal foil. From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the content of the liquid crystal polymer in Layer C is preferably 10% by mass to 99.99% by mass, more preferably 20% by mass to 99.9% by mass, even more preferably 30% by mass to 95% by mass, and particularly preferably 30% by mass to 90% by mass, relative to the total mass of Layer C.
[0066] The layer C may contain a filler. Preferred embodiments of the filler used in Layer C are the same as those of the filler used in Layer B, except as described below.
[0067] The layer C may contain additives other than the liquid crystal polymer and the filler. The preferred embodiments of the other additives used in the layer C are the same as the preferred embodiments of the other additives used in the layer A.
[0068] The average thickness of Layer C is preferably smaller than the average thickness of Layer A from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil. Average thickness T of layer A A and the average thickness T of layer C C T A / T C From the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the value of is preferably greater than 1, more preferably 1.5 to 100, further preferably 2 to 10, and particularly preferably 2 to 5. Also, the average thickness T of layer C C and the average thickness T of layer B B T C / T BFrom the viewpoints of the thermal expansion coefficient and the adhesion to the metal foil, the value of is preferably from 0.2 to 5, more preferably from 0.5 to 2, and particularly preferably from 0.8 to 1.2. Furthermore, from the viewpoints of the thermal expansion coefficient and adhesion to the metal foil, the average thickness of Layer C is preferably 3 μm to 40 μm, more preferably 5 μm to 30 μm, even more preferably 8 μm to 20 μm, and particularly preferably 10 μm to 15 μm. Furthermore, when layer C is a layer capable of volume expansion by an external stimulus, the average thickness of layer C is preferably thicker than the average thickness of a copper layer (copper wiring) disposed on the C layer side in a laminate described later.
[0069] The average thickness of the polymer film according to the present disclosure is preferably 6 μm to 200 μm, more preferably 12 μm to 100 μm, and particularly preferably 20 μm to 60 μm, from the viewpoints of strength, thermal expansion coefficient, and adhesion to metal foil.
[0070] The average thickness of the polymer film is determined by measuring any five points using an adhesive film thickness meter, for example, an electronic micrometer (product name "KG3001A" manufactured by Anritsu Corporation), and averaging these values.
[0071] From the viewpoint of the thermal expansion coefficient, the linear expansion coefficient of the polymer film according to the present disclosure is preferably from -20 ppm / K to 50 ppm / K, more preferably from -10 ppm / K to 40 ppm / K, further preferably from 0 ppm / K to 35 ppm / K, and particularly preferably from 10 ppm / K to 30 ppm / K.
[0072] In the present disclosure, the linear expansion coefficient is measured by the following method. Using a thermomechanical analyzer (TMA), a tensile load of 1 g is applied to both ends of a polymer film or each layer having a width of 5 mm and a length of 20 mm, and the film is heated from 25°C to 200°C at a rate of 5°C / min, cooled to 30°C at a rate of 20°C / min, and then heated again at a rate of 5°C / min. The linear expansion coefficient is calculated from the slope of the TMA curve between 30°C and 150°C.
[0073] <Method of manufacturing polymer film> [Film forming] The method for producing the polymer film according to the present disclosure is not particularly limited, and known methods can be referred to. Suitable methods for producing the polymer film according to the present disclosure include, for example, a co-casting method, a multi-layer coating method, a co-extrusion method, etc. Among these, the co-casting method is particularly preferred for producing a relatively thin film, and the co-extrusion method is particularly preferred for producing a thick film. When manufacturing by the co-casting method or the multi-layer coating method, it is preferable to carry out the co-casting method or the multi-layer coating method using a layer A-forming composition, a layer B-forming composition, a layer C-forming composition, etc., in which the components of each layer, such as a liquid crystal polymer, are dissolved or dispersed in a solvent.
[0074] Examples of the solvent include halogenated hydrocarbons such as dichloromethane, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, 1-chlorobutane, chlorobenzene, and o-dichlorobenzene; halogenated phenols such as p-chlorophenol, pentachlorophenol, and pentafluorophenol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and cyclohexanone; esters such as ethyl acetate and γ-butyrolactone; and ethylene carbonate. Examples of the organic solvent include carbonates such as propylene carbonate and propylene carbonate; amines such as triethylamine; nitrogen-containing heterocyclic aromatic compounds such as pyridine; nitriles such as acetonitrile and succinonitrile; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and urea compounds such as tetramethylurea; nitro compounds such as nitromethane and nitrobenzene; sulfur compounds such as dimethyl sulfoxide and sulfolane; and phosphorus compounds such as hexamethylphosphoramide and tri-n-butylphosphoric acid, and two or more of these may be used.
[0075] As the solvent, since it is less corrosive and easy to handle, a solvent mainly composed of an aprotic compound, particularly an aprotic compound having no halogen atom, is preferred, and the ratio of the aprotic compound to the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. In addition, as the aprotic compound, since it is easy to dissolve the liquid crystal polymer, it is preferred to use amides such as N,N-dimethylformamide, N,N-dimethylacetamide, tetramethylurea, and N-methylpyrrolidone, or esters such as γ-butyrolactone, and N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone are more preferred.
[0076] As the solvent, a solvent mainly composed of a compound having a dipole moment of 3 to 5 is preferred because it easily dissolves the liquid crystal polymer, and the proportion of the compound having a dipole moment of 3 to 5 in the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, a compound having a dipole moment of 3 to 5 is preferably used.
[0077] Furthermore, as the solvent, a solvent mainly composed of a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure is preferred because it is easy to remove, and the proportion of the compound having a boiling point of 220° C. or lower at 1 atmospheric pressure in the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, it is preferable to use a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure.
[0078] In addition, in the method for producing a polymer film according to the present disclosure, a support may be used when the film is produced by the above-mentioned co-casting method, multilayer coating method, co-extrusion method, etc. In addition, when a metal layer (metal foil) or the like used in a laminate described later is used as a support, the film may be used as it is without being peeled off. Examples of the support include a metal drum, a metal band, a glass plate, a resin film, and a metal foil. Among these, a metal drum, a metal band, and a resin film are preferred. An example of the resin film is a polyimide (PI) film. Examples of commercially available products include U-Pirex S and U-Pirex R manufactured by Ube Industries, Ltd., Kapton manufactured by DuPont-Toray Co., Ltd., and IF30, IF70, and LV300 manufactured by SKC Kolon PI. The support may have a surface treatment layer formed on its surface so that it can be easily peeled off. The surface treatment layer may be made of hard chrome plating, fluororesin, or the like. The average thickness of the resin film support is not particularly limited, but is preferably from 25 to 75 μm, and more preferably from 50 to 75 μm.
[0079] The method for removing at least a part of the solvent from the cast or coated film-like composition (cast film or coating film) is not particularly limited, and a known drying method can be used.
[0080] [Stretching] The liquid crystal polymer film according to the present disclosure can be appropriately combined with stretching in terms of controlling molecular orientation and adjusting the linear expansion coefficient and mechanical properties. The stretching method is not particularly limited, and known methods can be referred to. It may be performed in a state containing a solvent or in a dry film state. Stretching in a state containing a solvent may be performed by gripping the film and stretching it, or by using the self-shrinking force of the web due to drying without stretching it, or a combination thereof. Stretching is particularly effective for the purpose of improving the breaking elongation and breaking strength when the film brittleness is reduced by the addition of inorganic fillers, etc.
[0081] <Application> The polymer film according to the present disclosure can be used for various applications, and among others, can be suitably used as a film for electronic components such as printed wiring boards, and can be even more suitably used for flexible printed circuit boards. Furthermore, the polymer film according to the present disclosure can be suitably used as a polymer film for bonding metals.
[0082] (Laminate) The laminate according to the present disclosure may be any laminate in which the polymer film according to the present disclosure is laminated, but it preferably has the polymer film according to the present disclosure and a metal layer disposed on the surface of the polymer film on the Layer B side, and it is more preferable that the metal layer is a copper layer. Moreover, the laminate according to the present disclosure preferably comprises a polymer film according to the present disclosure having a Layer B, a Layer A, and a Layer C in this order, a metal layer disposed on the surface of the polymer film facing the Layer B, and a metal layer disposed on the surface of the polymer film facing the Layer C, and it is more preferable that both of the metal layers are copper layers. Furthermore, from the viewpoint of adhesion to the metal foil, the average thickness of the layer B is preferably larger than the average thickness of the metal layer (preferably the copper layer). From the viewpoint of adhesion to the metal foil, the average thickness of the layer C is preferably larger than the average thickness of the metal layer (preferably a copper layer) disposed on the surface on the layer C side. In addition, the metal layer arranged on the surface on the layer B side and the metal layer arranged on the surface on the layer C side may be metal layers of the same material, thickness and shape, or metal layers of different material, thickness and shape. From the viewpoint of characteristic impedance adjustment, the metal layer arranged on the surface on the layer B side and the metal layer arranged on the surface on the layer C side may be metal layers of different material and thickness, and a metal layer may be laminated on only one of the layers B and C. Furthermore, from the viewpoint of adjusting the characteristic impedance, a preferred embodiment is one in which a metal layer is laminated on one side of layer B or layer C, and another polymer film (preferably another liquid crystal polymer film) is laminated on the other side.
[0083] The peel strength between Layer B and the copper layer is preferably 0.5 kN / m or more, more preferably 0.7 kN / m or more, even more preferably 0.7 kN / m to 2.0 kN / m, and particularly preferably 0.9 kN / m to 1.5 kN / m. Furthermore, the peel strength between the layer C and the copper layer is preferably 0.5 kN / m or more, more preferably 0.7 kN / m or more, even more preferably 0.7 kN / m to 2.0 kN / m, and particularly preferably 0.9 kN / m to 1.5 kN / m.
[0084] In the present disclosure, the peel strength between layer B or layer C of a polymer film and a metal layer (eg, a copper layer) is measured by the following method. A peel test piece 1.0 cm wide is prepared from a laminate of a polymer film and a metal layer, the polymer film is fixed to a flat plate with double-sided adhesive tape, and the strength (kN / m) is measured when the metal layer is peeled from the polymer film at a speed of 50 mm / min using the 180° method in accordance with JIS C 5016 (1994).
[0085] The metal layer is preferably a copper layer. The copper layer is preferably a rolled copper foil formed by a rolling method or an electrolytic copper foil formed by an electrolytic method, and more preferably a rolled copper foil from the viewpoint of flex resistance.
[0086] The average thickness of the metal layer, preferably the copper layer, is not particularly limited, but is preferably 2 μm to 20 μm, more preferably 3 μm to 18 μm, and even more preferably 5 μm to 12 μm. The copper foil may be a carrier-attached copper foil formed on a support (carrier) in a peelable manner. As the carrier, a known carrier can be used. The average thickness of the carrier is not particularly limited, but is preferably 10 μm to 100 μm, and more preferably 18 μm to 50 μm.
[0087] The metal layer in the laminate according to the present disclosure may be a metal layer having a circuit pattern. In addition, it is also preferable to process the metal layer in the laminate according to the present disclosure into a desired circuit pattern by, for example, etching to form a flexible printed circuit board. The etching method is not particularly limited, and a known etching method can be used. EXAMPLES
[0088] The present disclosure will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the present disclosure is not limited to the specific examples shown below.
[0089] <<Measurement method>> [Expansion rate] The polymer film was cut with a microtome to prepare slice samples, and the thickness changes of layers A and B were measured using an optical microscope equipped with a heating stage system (HS82, Mettler Toledo). The initial thickness (t25) at 25°C and the thickness (t160) when heated to 160°C at a rate of 10°C / min were evaluated, and the value divided by the initial thickness (t160 / t25) was calculated as the expansion coefficient at 160°C (unit: %). The same calculation was performed for the case of 300°C.
[0090] [Thermal expansion coefficient] The film was cut with a microtome to prepare a section sample, which was then set in an optical microscope equipped with a heating stage system (HS82, Mettler Toledo). The temperature was then raised from 25 to 200°C at a rate of 5°C / min, cooled to 30°C at a rate of 20°C / min, and then raised again at a rate of 5°C / min. The thickness of layer B at 30°C (ts30) and the thickness of layer B at 150°C (ts150) were evaluated, and the value obtained by dividing the dimensional change by the temperature change ((ts150-ts30) / (150-30)) was calculated as the thermal expansion coefficient (αs) of layer B. The same calculation was performed for layer A.
[0091] [Dielectric tangent] The dielectric constant was measured by the resonance perturbation method at a frequency of 10 GHz. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd. CP531) was connected to a network analyzer (Agilent Technology Co., Ltd. "E8363B"), and a polymer film sample (width: 2.0 mm x length: 80 mm) was inserted into the cavity resonator. The dielectric constant and dielectric loss tangent of the polymer film sample were measured from the change in resonance frequency before and after insertion for 96 hours under an environment of 25°C temperature and 60% RH.
[0092] [Peel strength] A 1.0 cm wide peel test piece was prepared from the flexible wiring board described below, and the double-sided copper-clad laminate side was fixed to a flat plate with double-sided adhesive tape. The strength (kN / m) was measured when the single-sided copper-clad laminate side was peeled off at a speed of 50 mm / min using the 180° method in accordance with JIS C 5016 (1994).
[0093] <<Production Example>> <Liquid crystal polymer> LC-A: A liquid crystal polymer with a melting point of 315°C obtained by adjusting the heat treatment conditions with reference to the manufacturing example of liquid crystal polyester (B) in WO 2020 / 166644.
[0094] <Additives> A-1: A foaming agent consisting of the following mixture. A-1 was added so as to obtain the mass ratio shown in Table 1. Sodium bicarbonate: 5 parts by weight Sodium citrate: 5 parts by weight Talc: 1 part by weight
[0095] A-2: A foaming agent consisting of the following mixture. A-2 was added so as to obtain the mass ratio shown in Table 1. Sodium bicarbonate: 5 parts by weight Sodium citrate: 5 parts by weight Talc: 1 part by weight -Spinel-like silica sol (average particle size 35.8 nm) prepared according to the following method: 989 parts by weight
[0096] B-1: Commercially available silicone rubber powder with an average particle size of 5 μm (KMP-597, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0097] B-2: Additive consisting of the following mixture. B-2 was added so as to obtain the mass ratio shown in Table 1. Commercially available silicone rubber powder with an average particle size of 5 μm (KMP-597, manufactured by Shin-Etsu Chemical Co., Ltd.): 40 parts by weight - 10 parts by weight of confetti-like silica sol (average particle size 35.8 nm) prepared according to the following method
[0098] -How to make confetti-like silica sol- Water was added to 102.4 g of silica sol (Catalysts and Chemical Industries Co., Ltd.: Cataloid SI-40, average particle size 21.2 nm, SiO2 concentration 40.7% by mass) to make 4,170 g (SiO2 concentration 1% by mass), and a 5% by mass aqueous sodium hydroxide solution was added to adjust the pH of the silica sol to 11. Next, the temperature of the silica sol was raised to 80°C and maintained at 80°C for 30 minutes to obtain a core particle dispersion liquid (liquid A).
[0099] 575 g of water glass (manufactured by AGC Si-Tech Co., Ltd.: JIS No. 3 water glass, SiO2 concentration 24% by mass) was diluted with 2,185 g of water to prepare 2,760 g of an aqueous alkali silicate solution (liquid B). 2,450 g of an aqueous electrolyte solution was prepared by adding 2,352 g of water to 98.0 g of ammonium sulfate (manufactured by Mitsubishi Chemical Co., Ltd.) as an electrolyte. Then, the entire amount of the aqueous alkali silicate solution (liquid B) and the aqueous electrolyte solution were each added at 80°C over one hour to the entire amount of the core particle dispersion liquid (liquid A) maintained at a temperature of 80°C, thereby causing particle growth. Next, after aging at 80° C. for 1 hour, the core particle dispersion liquid in which particles had grown was washed with an ultrafiltration membrane until the pH became 10.8, and then concentrated to obtain a spinous silica sol with a SiO2 concentration of 20 mass%.
[0100] <Film forming> A film was formed according to the following co-casting method.
[0101] [Co-casting (solution casting)] -Preparation of polymer solution- The liquid crystal polymer shown in Table 1 was added to N-methylpyrrolidone, and stirred at 140°C for 4 hours under a nitrogen atmosphere to form a solution, which was then passed through a sintered fiber metal filter having a nominal pore size of 10 μm, and then through a sintered fiber filter also having a nominal pore size of 10 μm. The additives shown in Table 1 were then added, and the mixture was stirred at 25°C for 30 minutes to obtain a polymer solution. The solid content of the solution for layer A was 23 mass %, and that of the solution for layer B was 20 mass %.
[0102] -Preparation of polymer film and single-sided copper-clad laminate- The obtained polymer solution for layer A and the polymer solution for layer B were sent to a casting die equipped with a feed block adjusted for co-casting of a two-layer structure (layer A / layer B), and cast so that layer A was in contact with the treated surface of a low-roughness copper foil (manufactured by Fukuda Metal Foil and Powder Co., Ltd., CF-T4X-SV-12, thickness 12 μm). The solvent was removed from the cast film by drying at 40° C. for 4 hours, and a single-sided copper-clad laminate with a polymer film was obtained.
[0103] <Preparation of double-sided copper-clad laminate> -Precursor process for copper clad laminate- A low-roughness copper foil (CF-T4X-SV-12, thickness 12 μm, manufactured by Fukuda Metal Foil & Powder Co., Ltd.) was placed on the single-sided copper-clad laminate of Comparative Example 1 so that the treated side was in contact with the polymer film, and a lamination process was performed for 1 minute using a laminator (Vacuum Laminator V-130, manufactured by Nikko Materials Co., Ltd.) at 140°C and a lamination pressure of 0.4 MPa to obtain a precursor of a double-sided copper foil laminate.
[0104] -Main thermocompression bonding process- The obtained copper-clad laminate precursor was subjected to thermocompression bonding for 10 minutes under conditions of 300° C. and 4.5 MPa using a thermocompression bonding machine ("MP-SNL" manufactured by Toyo Seiki Seisakusho Co., Ltd.) to produce a double-sided copper-clad laminate.
[0105] <Fabrication of flexible wiring board> Using the resulting single-sided copper-clad laminate and double-sided copper-clad laminate, flexible wiring boards having a four-layer stripline structure with an outer plane (ground layer) were fabricated.
[0106] - Wiring substrate formation process - Using a known photofabrication technique, metal foil was patterned on one side of the above-mentioned double-sided copper-clad laminate to produce a wiring substrate (having a metal foil portion and a polymer film portion on its surface) including signal lines with a striped pattern of line and space (L / S) of 300 μm / 300 μm.
[0107] -Lamination process- The above wiring substrate and the above single-sided copper-clad laminate were used, and placed in a layer configuration of single-sided copper-clad laminate / wiring substrate so that the polymer film side of the single-sided copper-clad laminate was in contact with the signal line side of the wiring substrate, and laminated at 300°C using a vacuum press device to produce a flexible wiring substrate.
[0108] <<Evaluation>> The prepared polymer film was evaluated by the above-mentioned method, and the results are shown in Table 1. The dielectric tangent and the thermal expansion coefficient were measured using the single-sided copper-clad laminate as it was. The peel strength of the flexible wiring board was evaluated by cutting a 1.0 cm wide sample from the wiring substrate in the direction perpendicular to the stripe pattern. It is presumed that the lower limit of the peel strength is due to the polymer film portion of the wiring substrate.
[0109] [Table 1]
[0110] From the results shown in Table 1, the polymer films of Examples 1 to 4 according to the present disclosure have better adhesion to other polymer films and metal foils than the polymer film of Comparative Example 1. Note that the polymer film of Comparative Example 1 had a distribution in peel strength, with the peel strength being low at the portions where the films contacted each other. Moreover, from the results shown in Table 1, the polymer films of Examples 1 to 4 according to the present disclosure also have low dielectric tangents.
Claims
1. A layer A and a layer B on at least one surface of the layer A, The layer B is a layer capable of expanding in volume in response to an external stimulus, The dielectric tangent is 0.005 or less, The layer A and the layer B each contain a liquid crystal polymer, The difference in expansion coefficient between layer A and layer B at 160°C or 300°C due to the external stimulus is 0.1% or more; The external stimulus is heat. Polymer film.
2. A polymer film as described in claim 1, wherein layer B contains, in addition to the liquid crystal polymer, a polymer having a linear expansion coefficient larger than that of the liquid crystal polymer contained in layer A, or a foaming agent.
3. 3. The polymer film according to claim 1, wherein the layer B has an expansion coefficient of 3% or more at 300° C.
4. The polymer film according to any one of claims 1 to 3, wherein the expansion coefficient of the layer B at 300°C is greater than the expansion coefficient of the layer A at 300°C.
5. The polymer film according to any one of claims 1 to 4, wherein the thermal expansion coefficient αs of the layer B is greater than the thermal expansion coefficient αc of the layer A.
6. The polymer film according to any one of claims 1 to 5, further comprising a filler in any one of its layers.
7. The polymer film according to claim 6 , wherein the number density of the fillers is greater inside the polymer film than on the surface thereof.
8. The polymer film according to claim 6 or 7, wherein the layer B comprises a filler.
9. The polymer film according to claim 8 , wherein the layer B contains needle-like fillers or fillers having protrusions.
10. The polymer film according to any one of claims 1 to 9, wherein the polymer film has a linear expansion coefficient of -20 ppm / K to 50 ppm / K.
11. The polymer film according to any one of claims 1 to 10, wherein the polymer film has a dielectric loss tangent of 0.004 or less.
12. The polymer film according to any one of claims 1 to 11, wherein the liquid crystal polymer is a liquid crystal polymer having a constitutional repeating unit represented by any one of formulas (1) to (3). Formula (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Formula (3) -X-Ar 3 -Y- In formulas (1) to (3), Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, a biphenylylene group, or a group represented by the following formula (4), X and Y each independently represent an oxygen atom or an imino group, Ar 1 ~Ar 3 Each hydrogen atom in the group represented by the formula: may be independently substituted with a halogen atom, an alkyl group or an aryl group. Formula (4) -Ar 4 -Z-Ar 5 -[[]]END]] In formula (4), Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
13. Further comprising a layer C, The polymer film according to any one of claims 1 to 12, comprising the Layer B, the Layer A, and the Layer C in this order.
14. A laminate comprising the polymer film according to any one of claims 1 to 13 and a copper layer disposed on the surface of the polymer film on the layer B side.
15. The laminate according to claim 14, wherein the average thickness of the layer B is greater than the average thickness of the copper layer.
16. 16. The laminate according to claim 14 or 15, wherein the peel strength between the layer B and the copper layer is 0.5 kN / m or more.
17. A laminate comprising the polymer film according to claim 13, a copper layer disposed on a surface of the polymer film facing the layer B, and a copper layer disposed on a surface of the polymer film facing the layer C.
18. The laminate according to claim 17, wherein a peel strength between the layer C and the copper layer disposed on the surface on the layer C side is 0.5 kN / m or more.
Citation Information
Patent Citations
Electrical and electronic insulating adhesive tape
JP2003261845A
Peelable laminated film, peelable laminated film roll, manufacturing method thereof, film, optical film, polarizing plate, manufacturing method of polarizing plate, and liquid crystal display device
JP2013046992A
Method for manufacturing flexible copper-clad laminated sheet and flexible copper-clad laminated sheet
JP2017047686A
Liquid crystal polyester film, liquid composition containing liquid crystal polyester and method for manufacturing liquid crystal polyester film
JP2020026474A
Resin film, metal-clad laminate and circuit board
JP2021160148A